Screening approaches for the identification of Nrf2-Keap1 protein-protein interaction inhibitors targeting hot spot residues - Wataru Asano; Rie Hantani; Toru Uhara; François Debaene; Akihiro Nomura; Keishi Yamaguchi; Tsuyoshi Adachi; Kazuki Otake; Kazuhito Harada; Yoshiji Hantani (SLAS Discovery, 2024)
Protein-protein interactions (PPIs) play a crucial role in most biological processes and are important targets in the development of therapeutic agents. However, small molecule drug discovery that targets PPIs remains very challenging. Targeting hot spot residues is considered the best option for inhibiting such interactions, but there are few examples of how knowledge of hot spots can be used in high throughput screening to find hit compounds. A substrate adaptor protein for a ubiquitin ligase complex, Kelch-like ECH-associated protein 1 (Keap1), negatively modulates the expression of genes involved in cellular protection against oxidative stress. Here, we focused on three arginine hot spot residues in the Keap1 substrate binding pocket (Arg380, Arg415, and Arg483), and screened the carboxylic acid library owned by Japan Tobacco Inc. for compounds that interact with the arginine residues in differential scanning fluorescence assays. Furthermore, we identified several small molecule compounds that specifically bind to the Keap1 Kelch domain hot spots by comparing binding to alanine mutant proteins (R380A, R415A, and R483A) with binding to the wild-type protein using surface plasmon resonance (SPR) screening. These compounds inhibited the protein-protein interaction between the Keap1 Kelch domain and the nuclear factor erythroid 2-related factor 2 (Nrf2) peptide, and the ubiquitination of Nrf2 catalyzed by the Cul3/RINGBox 1 E3 ligase. In addition, the binding mode of one compound (Compound 4) was determined by X-ray crystallography after validation of binding by isothermal titration calorimetry, native mass spectrometry, and nuclear magnetic resonance. Compound 4 had favorable thermodynamic properties, and noncovalently bound to Keap1 with a stoichiometry of 1:1. Our results suggest that Compound 4 could potentially be developed into effective therapeutic or preventive agents for a variety of diseases and conditions such as oxidative stress response, inflammation, and carcinogenesis. We believe that the use of a set of complementary biophysical techniques including the SPR assay with single alanine mutant of hot spots provides opportunities to identify hit compounds for developing inhibitors of PPIs.